Olfaction in the Antarctic toothfish Dissostichus mawsoni: clues from the morphology and histology of the olfactory rosette and bulb - Sara Ferrando; Andrea Amaroli; Lorenzo Gallus; Davide Di Blasi; Erica Carlig; Marino Rottigni; Marino Vacchi; Steven J Parker; Laura Ghigliotti (Polar Biology, 2019)
The Antarctic notothenioid fish Dissostichus mawsoni (Antarctic toothfish) is an important piscine top predator in the Southern Ocean. Good olfactory capability has been hypothesized for this species on the basis of morphological (size of its olfactory bulb compared to other notothenioids) and behavioral (long distance migrations for food search and reproduc-tion) traits. Here, we provide new information on the structure and function of the olfactory rosette and bulb of D. mawsoniusing histology. Adult specimens (total length 136.2 ± 11.6 cm) were collected from McMurdo Sound. The rosettes had an average of 39 lamellae, without secondary folds and with a total surface area of about 1000 mm2. Both putative ciliated and microvillous receptor neurons were present in the sensory epithelium. Their projections to clustered glomeruli in the olfac-tory bulb were observed using antibodies against G-proteins. Numerous rodlet cells were observed in the epithelium and Gαi2-like immunoreactivity was present in their cytoplasm. This deserves further investigation given the still-debated nature of this cell type. Through the isotropic fractionator method, we showed 116,000 cells (mg of tissue)−1 in the olfactory bulb of D. mawsoni, a density that is similar to those found in mammals. Taken together, these data describe a well-developed olfactory system in this species, where olfaction is key sensory system